A Bibliometric Comparative Analysis of Domestic and International Research on Public Health Social Work - Zhijing HE; Shangman YAO; Zhizhong WANG (Yixue yu zhexue, 2025)
This paper analyzes the foundational research, hotspots, and future trends of public health social work research at home and abroad through knowledge graph analysis. The results reveal an uneven distribution of research, with the United States as the main research field. Compared with domestic research, international research started earlier, developed rapidly, and had a high cooperation density. Due to different national conditions and health policies, hotspots and trends of public health social work research at home and abroad are significantly different. International research focuses on social work and public health, concentrating on four themes: health, children, women and prevention. Since 2020, the global impact of the novel coronavirus has become another prominent area of focus. Domestic research, by contrast, concentrates on epidemic prevention and control, and discipline construction.